(untitled) (Journal of the College of Basic Education, 2026)
Imam al-Haythami and Imam al-Busiri are considered two of the most prominent hadith scholars, with the latter being a student of the former. Their books are generally distinguished by the inclusion of additions to the six or nine books, each according to his own methodology. Although I did not notice al-Busiri imitating his sheikh in his criticism of hadiths, discussion of them, and their verification of their authenticity, there are hadiths in which they both share the distinction of being additions. However, the difference in their methodologies in issuing hadith rulings reveals the breadth of their knowledge and their memorization of hadiths, to the point that they devoted books to adding hadiths, as well as the precision of their transmission and their trustworthiness in their careful attention to narrations from scholars, in order to arrive at hadith rulings, whether authentic, weak, or discontinued. I acquired samples from their two books, "Additions," and compared them with each other regarding the differences in hadith rulings. I concluded that each of them contributed their own unique insights into issuing these hadith rulings